Efficient cellular and humoral immune response and production of virus-neutralizing antibodies by the Hepatitis B Virus S/preS116-42 antigen - Pantazica, Ana-Maria; Dobrica, Mihaela-Olivia; Lazar, Catalin; Scurtu, Cristina; Tucureanu, Catalin; Caras, Iuliana; Ionescu, Irina; Costache, Adriana; Onu, Adrian; Clarke, Jihong Liu; Stavaru, Crina; Branza-Nichita, Norica (Frontiers in Immunology, 2022)
Despite the availability of improved antiviral therapies, infection with Hepatitis B virus (HBV) remains a significant health issue, as a curable treatment is yet to be discovered. Current HBV vaccines relaying on the efficient expression of the small (S) envelope protein in yeast and the implementation of mass vaccination programs have clearly contributed to containment of the disease. However, the lack of an efficient immune response in about 10% of vaccinated people, the controversies regarding the persistence of seroprotection in vaccine responders and the emergence of vaccine escape virus mutations urge for the development of better HBV immunogens. Due to the critical role played by the preS1 domain of the large (L) envelope protein in HBV infection and the ability to trigger virus neutralizing antibodies, including this protein in novel vaccine formulations has been considered a promising strategy to overcome the limitations of S only-based vaccines. In this work we aimed to combine relevant L and S epitopes in chimeric antigens, by inserting preS1 sequences within the external antigenic loop of S, followed by production in mammalian and detailed analysis of their antigenic and immunogenic properties. Of the newly designed antigens, the S/preS1 16–42 protein assembled in subviral particles (SVP) and showed the highest expression and secretion levels, therefore it was selected for further studies in vivo. Analysis of the immune response induced in mice vaccinated with S/preS1 16–42- and S-SVPs, respectively, demonstrated enhanced immunogenicity of the former and its ability to activate both humoral and cellular immune responses. This combined activation resulted in production of neutralizing antibodies against both wild-type and vaccine-escape HBV variants. Our results validate the design of chimeric HBV antigens and promote the novel S/preS1 protein as a potential vaccine candidate for administration in poor-responders to current HBV vaccines.